Expression of CRYM in different rat organs during development and its decreased expression in degenerating pyramidal tracts in amyotrophic lateral sclerosis. Issue 3 (30th March 2018) - Hommyo, Reiji; Suzuki, Satoshi O.; Abolhassani, Nona; Hamasaki, Hideomi; Shijo, Masahiro; Maeda, Norihisa; Honda, Hiroyuki; Nakabeppu, Yusaku; Iwaki, Toru
Abstract : The protein μ‐crystallin (CRYM) is a novel component of the marsupial lens that has two functions: it is a key regulator of thyroid hormone transportation and a reductase of sulfur‐containing cyclic ketimines. In this study, we examined changes of the expression pattern of CRYM in different rat organs during development using immunohistochemistry and immunoblotting. As CRYM is reportedly expressed in the corticospinal tract, we also investigated CRYM expression in human cases of amyotrophic lateral sclerosis (ALS) using immunohistochemistry. In the rat brain, CRYM was expressed in the cerebral cortex, basal ganglia, hippocampus and corticospinal tract in the early postnatal period. As postnatal development progressed, CRYM expression was restricted to large pyramidal neurons in layers V and VI of the cerebral cortex and pyramidal cells in the deep layer of CA1 in the hippocampus. Even within the same regions, CRYM‐positive and negative neurons were distributed in a mosaic pattern. In the kidney, CRYM was expressed in epithelial cells of the proximal tubule and mesenchymal cells of the medulla in the early postnatal period; however, CRYM expression in the medulla was lost as mesenchymal cell numbers decreased with the rapid growth of the medulla. In human ALS brains, we observed marked loss of CRYM in the corticospinal tract, especially distally. Our results suggest that CRYM may play roles in development of cortical and hippocampal pyramidal cells in the early postnatal period, and in the later period, performs cell‐specific functions in selected neuronal populations. In the kidney, CRYM may play roles in maturation of renal function. The expression patterns of CRYM may reflect significance of its interactions with T3 or ketimines in these cells and organs. The results also indicate that CRYM may be used as a marker of axonal degeneration in the corticospinal tract.